The Urgency of Program Evaluation in the Implementation of Inclusive Education in Public Elementary Schools in Jatiuwung District Tangerang City - Adzka Azzamulhaq; Asep Supena; Indra Jaya (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the challenges in the implementation of inclusive education in public elementary schools in Jatiuwung District, Tangerang City, and to analyze the urgency of program evaluation as a strategic effort to improve the quality and sustainability of inclusive education services. Methodology: This study employed a qualitative approach using a case study method. Data were collected through observations, in-depth interviews, and document analysis involving principals, classroom teachers, and special education teachers from inclusive elementary schools. The data were analyzed using descriptive qualitative techniques through data reduction, data display, and conclusion drawing. Main Findings: The findings reveal that the implementation of inclusive education has been carried out; however, it continues to face significant challenges, including limited teacher competence in addressing students with special educational needs, an insufficient number of special education teachers, inadequate inclusive learning facilities and infrastructure, and the absence of systematic and continuous program evaluation. These conditions reduce the effectiveness of inclusive education implementation and indicate the need for comprehensive evaluation to support continuous program improvement. Novelty/Originality of this study: This study offers a novel perspective by examining inclusive education from the standpoint of program evaluation rather than focusing solely on implementation practices or teacher readiness. It highlights the relationship between implementation challenges and the necessity of systematic program evaluation as a foundation for improving inclusive education services, particularly within the context of public elementary schools in Jatiuwung District, Tangerang City, an area that has received limited attention in previous studies.